2017
DOI: 10.1002/2017gl073087
|View full text |Cite
|
Sign up to set email alerts
|

Mass balance reassessment of glaciers draining into the Abbot and Getz Ice Shelves of West Antarctica

Abstract: We present a reassessment of input‐output method ice mass budget estimates for the Abbot and Getz regions of West Antarctica using CryoSat‐2‐derived ice thickness estimates. The mass budget is 8 ± 6 Gt yr−1 and 5 ± 17 Gt yr−1 for the Abbot and Getz sectors, respectively, for the period 2006–2008. Over the Abbot region, our results resolve a previous discrepancy with elevation rates from altimetry, due to a previous 30% overestimation of ice thickness. For the Getz sector, our results are at the more positive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 56 publications
4
25
2
Order By: Relevance
“…Glaciers feeding the Getz and Sulzberger ice shelves (B20; including Berry, Hull and Land glaciers) increased in speed by 10 to 100 m yr −1 at their grounding lines, increasing discharge by 6 % (Table 2). This result is in broad agreement with Chuter et al (2017) that observed increases in ice velocity during the 2007-2013 period alongside 2010-2013 dynamic thinning rates of 0.7 m yr −1 for the glaciers feeding the Abbot and Getz ice shelves.…”
Section: Amundsen Seasupporting
confidence: 81%
See 4 more Smart Citations
“…Glaciers feeding the Getz and Sulzberger ice shelves (B20; including Berry, Hull and Land glaciers) increased in speed by 10 to 100 m yr −1 at their grounding lines, increasing discharge by 6 % (Table 2). This result is in broad agreement with Chuter et al (2017) that observed increases in ice velocity during the 2007-2013 period alongside 2010-2013 dynamic thinning rates of 0.7 m yr −1 for the glaciers feeding the Abbot and Getz ice shelves.…”
Section: Amundsen Seasupporting
confidence: 81%
“…10), summing to a total imbalance of −214 ± 51 Gt yr −1 with largest rates of loss collocated with increased glacier velocities along the Amundsen Sea Embayment (B21 and B22) and Getz Ice Shelf (B20). The large mass loss for the Getz Ice Shelf region is in contrast to the near balance conditions recently reported by Chuter et al (2017) for the 2006-2008 period but is in agreement with the 2010-2013 estimate of net mass change by Martín-Español et al (2016). The East Antarctic Ice Sheet is found to have increased slightly in mass at a rate of 61 ± 73 Gt yr −1 with largest gains in Dronning Maud (B6) and Enderby Land (B7 and B8) that can be partially attributed to increase in precipitation rate (+28 Gt yr −1 relative to 1979-2007 mean) during the study period, which is consistent with earlier findings (Boening et al, 2012;Shepherd et al, 2012).…”
Section: Changes In Net Mass Balancecontrasting
confidence: 48%
See 3 more Smart Citations